Sarcoidosis and lymphoma mortality risk: An observational study from the Spanish National Registry - Moreno-Torres, Víctor; Martínez-Urbistondo, María; Durán-del Campo, Pedro; Tutor, Pablo; Rodríguez, Begoña; Castejón, Raquel; Mellor-Pita, Susana (Journal of Translational Autoimmunity, 2025)
Introduction: Patients with sarcoidosis have a lower survival rate than the general population, in part due to cardiovascular disease, infections and neoplasms. Our objective was to evaluate the impact of haematological neoplasms (HN) and lymphomas on sarcoidosis patient mortality in a nation-wide analysis conducted in Spain, a country with a population of 47 million. Methods: Retrospective and observational comparison of the HN related deaths in sarcoidosis patients and the general Spanish population reported in the Spanish Hospital Discharge Database. To determine the impact of sarcoidosis on the risk of dying from each HN lineage, a binary logistic regression considering age, female sex, tobacco and alcohol consumption, was performed. Results: In the period 2016 and 2019, 139,531 in-hospital deaths from neoplasms were certified in Spain (77 in patients with sarcoidosis). Patients with sarcoidosis died at younger age than the general Spanish population (72.9 vs 77.6, p<0.001). Sarcoidosis patients presented a higher mortality risk from HN (20.8% vs 8.9%, p=0.001, OR=2.64, 95% CI 1.52-4.59), attributable to the higher proportion of deaths from non-Hodgkin lymphoma (NHL), (9.2% vs 2.9%, p=0.006, OR= 3.33, 95% CI 1.53-7.25) from both B cell (6.6% vs 2.5%, p=0.044, OR= 2.62, 95% 1.06-6.5) and T/NK cell lineages (2.6% vs 0.3%, p=0.024, OR= 7.88, 95% CI 1.92-32.29) as well as HN with uncertain behavior and myeloproliferative disorders (2.6% vs 0.3%, p=0.018, OR= 11.88, 95% CI 2.88-49.02). The mean age of sarcoidosis patients who died from HN (63.6 vs 71.9, p=0.032) and non-Hodgkin lymphoma (56.9 vs 71, p=0.009) was lower than that of the general population Conclusion: Patients with sarcoidosis present a higher risk of premature death from HN, including NHL from B, T/NK cell lineage and myeloproliferative disorders in comparison with the general Spanish population. In addition to developing strategies that might help to attenuate their occurrence and impact, such as decreasing the immunosuppressive burden, specific early-detection programs for these conditions should be investigated and considered carefully.
Keywords: sarcoidosis; haematological neoplasm; lymphoma; mortality; sarcoidosis-lymphoma syndrome